A study on the association of mood disorders and gluten-related diseases. (February 2018) - Porcelli, Brunetta; Verdino, Valeria; Ferretti, Fabio; Bizzaro, Nicola; Terzuoli, Lucia; Cinci, Francesca; Bossini, Letizia; Fagiolini, Andrea
Abstract: Our study aimed to evaluate the presence of antibodies related to gluten intolerance in patients with mood disorders. A total of 60 patients with a diagnosis of bipolar disorder or depressive disorder were recruited. Fourty-eight subjects randomly selected among unrelated family members were included as controls. Celiac disease-associated antibodies were assayed both in the patients and controls. Mean values of IgA/IgG anti-gliadin antibodies, IgA/IgG anti-deamidated gliadin peptide antibodies and IgA anti-transglutaminase (tTG) antibodies were not different between patients and controls. However, a significant difference was found for anti-tTG IgG antibodies. Even if both in controls and in patients the mean anti-tTG IgG value was below the cutoff, the estimates produced by the statistical model showed that each unit increase in the anti-tTG IgG antibody value corresponded to an approximately 5% increased chance of having a mood disorder. The patient group showed a more frequent presence of symptoms associated to non-celiac gluten sensitivity. However, as there was neither any correlation between antibody levels and gastrointestinal symptoms, nor with the intensity of the psychiatric symptoms, it may be conceivable that the increase in anti-tTG IgG antibodies is not disorder-related but possibly an outcome of the psychiatric disorder itself. Highlights: Anti-tTG IgG antibodies seem to be the most characteristic antibody in mood disorders. Autoimmune comorbidity is not responsible of higher levels of anti-tTG IgG antibodies in mood disorders. High levels of anti-tTG IgG could be predisposing factor for psychiatric disorder.